Free tissue transfer for central skull base defect reconstruction: Case series and surgical technique. (April 2021) - Sagheer, S. Hamad; Swendseid, Brian; Evans, James; Rabinowitz, Mindy; Nyquist, Gurston; Rosen, Marc R.; Toskala, Elina; Heffelfinger, Ryan; Luginbuhl, Adam J.; Curry, Joseph M.
Highlights: Free flap reconstruction of the central skull base is difficult. Four approaches are transmaxillary, transoral, parapharyngeal, and retropharyngeal. Post-surgical complications may arise. Abstract: Objectives: Local reconstruction of central skull base defects may be inadequate for large defects or reoperative cases; free tissue transfer may be necessary. Inset of the flap and management of the pedicle can be challenging. We report our experience and approaches. Methods: Retrospective review identifying seven patients with central skull base defects who underwent free flap reconstruction from 2016 to 2020. Results: Four patients with recurrent nasopharyngeal carcinoma, one with recurrent craniopharyngioma, one with clival-cervical chordoma, and one with meningioma of the middle cranial fossa were analyzed. Six defects were closed with an anterolateral thigh free flap and one with a radial forearm free flap. In two patients, the flap was secured in an onlay fashion to the defect via a Caldwell-Luc transmaxillary approach. In one patient, the flap was passed transorally, and the pedicle was delivered into the neck via Penrose drain. In two patients, a parapharyngeal technique and in two others, a retropharyngeal was used for nasopharyngeal inset with endoscopic assistance. There were no flap failures, with an average follow-up time of 20.1 (range 3.2–47.1) months. One patient required flap repositioning on postoperative day three due to midline shift and intracranial contents compression. The transoral inset flap necessitated flap repositioning on postoperative day 13 to improve the nasopharyngeal airway. Conclusion: Free flap reconstruction of the central skull base is challenging, but transmaxillary, transoral, parapharyngeal, and retropharyngeal approaches can be used with endoscopic assistance to ensure secure inset flap and avoid airway obstruction.